Lipid and fatty acid turnover of the pteropods Limacina helicina, L. retroversa and Clione limacina from Svalbard waters - Boissonnot, L; Niehoff, B; Ehrenfels, B; Søreide, JE; Hagen, W; Graeve, M (Marine Ecology Progress Series, 2019)
This study aimed at a better understanding of the fatty acid (FA) turnover in Arctic pteropods. Thecosome pteropods, i.e. Limacina helicina (juveniles and adults) and L. retroversa (adults), were collected in summer/autumn in Kongsfjorden and Isfjorden (Svalbard, 78° N) and, for the first time, successfully fed with 13 C-labeled algae for 6 d. The gymnosome pteropod Clione limacina was sampled in summer in northern Svalbard and fed with 13 C-labeled L. retroversa for 23 d. FA compositions were determined by gas chromatography, and 13 C enrichment of FAs was analyzed by compound-specific isotope analysis. Among the thecosomes, maximum lipid turnover occurred in L. retroversa adults (1.3% d −1 ). L. helicina adults and juveniles showed lower lipid turnover rates (0.1 and 0.2% d −1 , respectively). The thecosomes exhibited the ability to assimilate omega-3 FAs (up to 8.0% d −1 ). The lipid turnover rate of C. limacina averaged at only 0.07% d −1 . However, C. limacina clearly showed the unusual capacity of de novo synthesis of odd-chain FAs (up to 1.2% d −1 ). Lipid turnover rates of pteropods were lower than those reported for Arctic copepods. However, pteropods may play a substantial role in the transfer of lipids to higher trophic levels, especially in autumn, when copepods have descended from the upper layers of the water column. The pteropods also showed the capacity to channel particular compounds such as omega-3 and odd-chain FAs, and therefore could be important for the functional diversity of the Arctic zooplankton community.